No Straight Lines Local Leadership and the Path from Government to Governance in Small Cities - Kading, Terry (Small Cities Sustainability Studies in Community and Cultural Engagement, 2018)
Small cities face intricate challenges. No Straight Lines provides the basis for a refined model of community-engaged leadership and research designed to realize equality of quality of life. With particular attention to the small city of Kamloops, BC, this book explores the impact of extended, short-term, and unique leadership collaborations and local responses to homelessness, sustainability and food security, aging populations, and the recovery of local history. It offers exciting insights into the role of the university in the small city, from generating local learning opportunities to the integration of undergraduates and faculty in achieving positive change. Based on active engagement, No Straight Lines reveals the obstacles present in addressing local needs, and the transformations that can be achieved through effective collaboration. It offers rich accounts and valuable insights into flexible practices that respond to the needs of community organizations while recognizing the challenges associated with resource constraints and limitations in capacity. This unique collection provides new insights into the barriers and benefits of leadership and learning in the small city. With Contributions By: Ginny Rastoy, Lisa Cooke, Robin Reid, Kendra Besanger, Dawn Farough, Tina Block, and Terry Kading